Bridging generations: Virginia Woolf and Quentin Bell's intergenerational collaboration in ‘A life of Vanessa Bell’ - Guilherme Magri da Rocha; Diana Navas (Acta Scientiarum. Language and Culture, 2026)
This article examines the collaborative authorship of ‘A Life of Vanessa Bell’ within the Charleston Bulletin Supplements, an intergenerational project by Virginia Woolf and her nephew Quentin Bell. Situated at the crossroads of modernist aesthetics, family literary traditions, and children’s literature, this study explores how their partnership redefines traditional ideas of childhood, authorship, and literary form. The research looks at the interaction between Woolf’s fragmented, playful narrative and Bell’s illustrations, highlighting how their collaboration represents modernist experimentation and questions hierarchical structures of adult authority. The findings show how text and image come together to create a crossover cultural artifact.